Conselho Editorial (Secretariado Executivo em Revist@, 2014)
Secretariado Executivo em Revist@Nº 9/2013ISSN 1809-2802Acesso: www.upf.br/seer www.upf.br/secretariadoConselho editorial desta edição:Profa. Dra. Carla Maria SchmidtProfa. Ma. Chussy Karla Souza AntunesProfa. Ma. Daniela Giareta DuranteProf. Dr. Erivaldo Pereira do NascimentoProfa. Ma. Fabiana Regina BiscoliProfa. Ma. Gisele Benck de MoraesProfa. Ma. Ivanete Daga CieloProfa. Ma. Rosimeri Ferraz SabinoProfa. Ma. Susana Elisabeth Neumann Organização:Profa. Ma. Josete Alzira Passamani Stocco